Emotional Brand Attachment as a Pathway to Brand Nostalgia, Brand Involvement and Brand Forgiveness - Hongthong, Patcharee; Jaroenwanit, Pensri; Nelson, James E.; Khalid, Bilal (International Review of Management and Marketing, 2025)
This study explores the relationships between Emotional Brand Attachment (EBA), Brand Nostalgia, Brand Involvement, and Brand Forgiveness, focusing on their roles in consumer-brand recovery dynamics. Using Emotional Brand Attachment Theory and Structural Equation Modeling (SEM), the findings reveal that EBA strongly influences Brand Involvement and directly contributes to Brand Forgiveness, while Brand Involvement serves as a key mediator in restoring trust. However, Brand Nostalgia shows minimal direct impact on forgiveness, highlighting its context-dependent nature. These insights emphasize the importance of fostering emotional connections and consumer involvement in brand recovery strategies, while suggesting that the effectiveness of nostalgia may vary across scenarios. The study provides actionable recommendations for leveraging emotional attachment and involvement in post-failure brand management while encouraging further exploration of contextual influences.